AB1155 Immunoglobulin g4 – related disease, a diagnostic challenge. (12th June 2018) - Diéguez, P.; Gimena, B.; Argibay, A.; Vázquez Triñanes, C.; Estévez, M.; Freire, M.; Fernández Martín, J.; Rivera, A.
Abstract : Background: The IgG4-related disease (IgG4-RD) is a chronic, inflammatory, multi-organic, systemic disease. The pathological assessment is the gold standard for the diagnosis, hallmarked by the lymphoplasmacytic tissue infiltration of mainly IgG4-plasma cells, the storiform fibrosis and the obliterative phlebitis. Objectives: The aim of this study was to analyse the features of IgG4- RD cases followed in a specific autoimmune diseases unit, since 2013. Methods: Descriptive, retrospective study, through the review of clinical charts. Medical records were reviewed for demographics information, clinical presentation, underlying conditions, laboratory and radiological data, medical and surgical treatments and clinical outcomes. All patients diagnosed by biopsy were included (international consensus pathological criteria of 2012). We excluded the possible cases of IgG4-RD when biopsy was not available or did not meet the criteria previously mentioned. Results: Eight patients with characteristic clinical, histological and laboratory features of IgG4-RD were included. The patients were predominantly male (87.5%), the mean age at diagnosis was 66±11 years. 48–80 87.5% of the cases were consulted from other hospital Services, mainly surgical: Urology 25% (hydrocele and urinary retention), General Surgery 25% (obstructive jaundice and forearm tumour), Vascular Surgery 25% (abdominal aortic aneurysm), Cardiac Surgery 12.5% (thoracic aortic aneurysm) and Neurology 12.5% (hypertrophic pachymeningitis). The most commonly involved organs were vascular 87.5% (6 aorta, 1 pulmonary veins) and retroperitoneum 75%, followed by renal 37.5%, pancreatic 12.5%, and central nervous system 12.5%. It was found isolated organic involvement in only one patient (autoimmune pancreatitis). Two patients had previous malignancy: renal cells and prostate. Magnetic resonance imaging, computed tomography and FDG-PET were made in 62.5% each of them. Serum IgG4 was determined in all cases, 62.5% of patients had normal IgG4 serum levels (the upper limit of normal for serum IgG4 is 135 mg/dl). Three patients (37.5%) had elevated serum IgG4, the mean level was 188±38 mg/dL ((152–266). The pathological findings were dense lymphoplasmacytic infiltrate in 6 cases (75%) with obliterative phlebitis in 5 of them, storiform-type fibrosis in 4 cases (50%) and IgG4/IgG ratio >40% in 75% of the samples. Glucocorticoids treatment was initiated in 75% of patients, 25% were untreated for predominantly fibrotic involvement. There were treatment response in 60% of cases. 25% had a relapse after corticoid withdrawal. Only one patient received a second drug due to lack of response to Prednisone (rituximab). Conclusions: According to the literature, IgG4-RD patients were predominantly male in their sixth and seventh decade of life. The predominant involvement in our serie was vascular and retroperitoneal, with no cases of glandular manifestations. Highlight the high number of cases with normal serum IgG4. Most of our patients responded to corticosteroid therapy. Disclosure of Interest: None declared